Clostridial conversion of corn syrup to Acetone-Butanol-Ethanol (ABE) via batch and fed-batch fermentation. Issue 3 (March 2019) - Niglio, Saverio; Marzocchella, Antonio; Rehmann, Lars
Abstract: Corn syrup - a commercial product derived from saccharification of corn starch - was used to produce acetone-butanol-ethanol (ABE) by Clostridium spp. Screening of commercial Clostridium spp., substrate inhibition tests and fed-batch experiments were carried out to improve ABE production using corn syrup as only carbon source. The screening tests carried out in batch mode using a production media containing 50 g/L corn syrup revealed that C. saccharobutylicum was the best performer in terms of total solvent concentration (12.46 g/L), yield (0.30 g/g) and productivity (0.19 g/L/h) and it was selected for successive experiments. Concentration of corn syrup higher than 50 g/L resulted in no solvents production. Fed-batch fermentation improved ABE production with respect to batch fermentation: the butanol and solvent concentration increased up to 8.70 and 16.68 g/L, respectively. The study demonstrated the feasibility of producing solvents via ABE fermentation using corn syrup as a model substrate of concentrated sugar mixtures.